Movements, Habitat Use, and Diving Behavior of Shortfin Mako in the Atlantic Ocean - Santos, Catarina C.; Domingo, Andrés; Carlson, John; Natanson, Lisa J.; Travassos, Paulo; Macías, David; Cortés, Enric; Miller, Philip; Hazin, Fábio; Mas, Federico; Ortiz de Urbina, Josetxu; Lino, Pedro G.; et al. (Frontiers in Marine Science, 2021)
The shortfin mako is one of the most important shark species caught in Atlantic Ocean pelagic fisheries. Given increasing concerns for the stock status of the species, the present study was designed to fill gaps in the knowledge of habitat use and movement patterns of shortfin mako in the Atlantic Ocean. From 2015 to 2019, 53 shortfin makos were tagged with pop-up satellite archival tags within the North, Central, and Southwest Atlantic Ocean, with successful transmissions received from 34 tags. Generally, sharks tagged in the Northwest and Central Atlantic moved away from tagging sites showing low to no apparent residency patterns, whereas sharks tagged in the Northeast and Southwest Atlantic spent large periods of time near the Canary Archipelago and Northwest Africa, and over shelf and oceanic waters off southern Brazil and Uruguay, respectively. These areas showed evidence of site fidelity and were identified as possible key areas for shortfin mako. Sharks spent most of their time in temperate waters (18–22°C) above 90 m; however, data indicated the depth range extended from the surface down to 979 m, in water temperatures ranging between 7.4 and 29.9°C. Vertical behavior of sharks seemed to be influenced by oceanographic features, and ranged from marked diel vertical movements, characterized by shallower mean depths during the night, to yo-yo diving behavior with no clear diel pattern observed. These results may aid in the development of more informed and efficient management measures for this species.